(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background: Pesticide poisoning kills hundreds of thousands of people in the Asia Pacific region each year. The majority are from deliberate self-poisoning with organophosphorus pesticides (OP),paraquat etc. It is a critical health problem in rural areas, where hazardous pesticides are easily available. Very few studies were present regarding this in India and research on anti-dotes to commonly available pesticides is very minimal. According to WHO report, it is the 2nd most common cause of death among people aged 15-29 years. Methodology: An observational study was conducted to study suicidal poisoning cases from Jan-June 2022 in a retrospective record-based manner.Qualitative variables were represented with graphs and tables. Quantitative variables were represented with mean and Standard deviation. Multinomial logistic regression was done to test the significance of poisoning agents with survival status. Nagelkerke R-squared mean regression model was considered in the analysis. p-value less than 0.05 was considered significant. Results: The incidence of suicidal poisoning was 696( 0.46%) during the study period. The mean age of the study population is 32.5±12.3 years. Majority of the cases were Organophosphorus compounds and paraquat comprising a total of about 26.11%. Fatality rate was 17.4% Multinomial logistic regression of various poisoning agents showed high significance of mortality OP poisoning(p=0.03), Paraquat poisoning (p<0.001) and Herbicides(p=0.02). Conclusion: Young populations were more prone to commit suicide suggesting increased recognition of the need for a coordinated response involving public health officials and psychiatric specialists to conduct mental health awareness camps and to provide counselling. Strengthening of translational research to develop anti-dotes for commonly available pesticides.